(3GbJUGOjGJ JfejI GdehGQO GdHTQjI (B/s - (3NWGH, CSYOs ((3GdbGgQI(B: s (3OGQ GdcJGH GdMOjK(B, s, 2008)
(3GdJfejI GdHTQjI aj GdSjGb GdeLJeYj(B- (3GdJfejI GdHTQjI (B( (3eaghe hechfGJ(B) - (3eMGhQ GdJfejI GdHTQjI aj GdhWf GdYQHj(B- (3GdeJZjQGJ GdELJeGYjI GdeDKQI aj YdGbI GdJYdje HGdYed aj GdhWf GdYQHj(B- (3GdCHYGO GdKbGaI ddJfejI GdHTQjI aj GdhWf GdYQHj(B- (3JUhQGJ ChdjI dJbjje GdJYdje aj OhdI GdchjJ(B- (3eDTQGJ EMUGFjI ddJfejI GdHTQjI YGeI hGdhWf GdYQHj NGUIs
Keywords: (3GbJUGOjGJ GdJfejIs; (3Gdbhi GdYGedIs; (3GdehGQO GdHTQjIs; (3JfejI GdehGQO GdHTQjIs